Designation of Autoinflammatory Skin Manifestations With Specific Genetic Backgrounds - Kanazawa, Nobuo (Frontiers in Immunology, 2020)
“Autoinflammatory disease (AiD)” has first been introduced in 1999 when the responsible gene for the familial Hibernean fever or autosomal dominant-type familial Mediterranean fever-like periodic fever syndrome was reportedly identified as tumour necrosis factor receptor superfamily 1. Linked with the rapid research progress in the field of innate immunity, “autoinflammation” has been designated for dysregulated innate immunity in contrast to “autoimmunity” with dysregulated acquired immunity. As hereditary periodic fever syndromes represent the prototype of AiD, monogenic systemic diseases are the main members of AiD. However, skin manifestations provide important clinical information and there are even some AiDs originating from skin diseases. Recently, AiD showing psoriasis and related keratinization diseases have specifically been designated as “autoinflammatory keratinization diseases (AiKD)” and CARD14-associated psoriasis and deficiency of interleukin-36 receptor antagonist previously called as generalized pustular psoriasis are included. Similarly, a number of autoinflammatory skin diseases can be proposed; autoinflamatory urticarial dermatosis (AiUD) such as cryopyrin-associated periodic syndrome; autoinflammatory neutrophilic dermatosis (AiND) such as pyogenic sterile arthritis, pyoderma gangrenosm, and acne syndrome; autoinflammatory granulomatosis (AiG) such as Blau syndrome; autoinflammatory chilblain lupus (AiCL) such as Aicardi-Goutieres syndrome; autoinflammatory lipoatrophy (AiL) such as Nakajo-Nishimura syndrome; autoinflammatory angioedema (AiAE) such as hereditary angioedema; and probable autoinflammatory bullous disease (AiBD) such as granular C3 dermatosis. With these designations, skin manifestations in AiD can easily be recognized and, even more importantly, autoinflammatory pathogenesis of common skin diseases are expected to be more comprehensive.